Effects of Hand-Arm Bimanual Intensive Training on Fine Motor Skills in Patients of Chronic - Aisha Munawar, Pakeeza Seemal, Hamna Afzal, Amna Yaseen, Tooba Ashraf, Ayesha Amjad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the effects of Hand-arm Bimanual Intensive Training on fine motor skills of chronic stroke patients. Methods: A randomized control trail was conducted at District Head Quarter Hospital Sargodha. Twenty-eight stroke patients were randomized into 2 groups. All patients were examined by using Questionnaire of Disabilities of Arm, Shoulder, and Hand (DASH), Action Research Arm Test (ARAT) and Wolf Motor Function Test (WMFT). Control group was treated with Conventional Physical Therapy and experimental group with Hand Arm Bimanual Intensive Training. There were 3 sessions every week for a total of 12 sessions over the course of 4 weeks. At the beginning of the intervention, two weeks later, and four weeks later, all outcomes were evaluated. Data analysis was done with SPSS version 21. Results: Intra group analysis showed statistically significant results (p<0.001) in each group after 4 weeks of treatment indicating improvement in Disabilities of Arm, Shoulder, and Hand (DASH), Action Research Arm Test (ARAT) and Wolf Motor Function Test (WMFT) of both groups. However, based on their mean differences, experimental group demonstrated greater progress across all outcome measures which is indicated through Inter group analysis that statistically significant difference was present between two groups in DASH, ARAT and WMFT with p-values 0.045, 0.046 and 0.043 respectively at end of treatment. Practical implications: HABIT pays attention to bimanual training which is highly related to most ADL tasks so there is need to evaluate the effectiveness of HABIT-related interventions. This will help to promote improvements in upper extremity functions and to enhance the level of independence among stroke patients. Conclusion: Study concluded that both conventional physical therapy and hand arm bimanual intensive training (HABIT) are helpful in improving upper extremity fine motor abilities in chronic stroke patients, but HABIT is more beneficial as compared to usual conventional and routine rehab treatments. Keywords: HABIT, fine motor skills, physical therapy, upper extremity, stroke